INFLUENCE OF LEADERSHIP, ORGANIZATIONAL CULTURE AND DIGITAL CAPABILITIES TO EMPLOYEE PERFORMANCE AT PT. PLN (PERSERO) ULP PALOPO KOTA - Marhum, Nirwandani; Maszudi, Edi; Adil, Adil (Distribusi - Journal of Management and Business, 2025)
This study aims to determine the influence of leadership, organizational culture, and digital skills on employee performance at PT. PLN (Persero) ULP Palopo City. This study uses a quantitative method. Data collection techniques; primary data and secondary data. Primary data was taken by distributing questionnaires to respondents. The number of employees at PT. PLN (Persero) ULP Palopo Kota is 35 people. The total population in this study is 35 employees. The number of respondents in this research is 35 employees - all employees are made respondents (census). The measurement scale used is the Likert scale. The data analysis technique used is SPSS Statistical Analysis 22. The results of this study show that (1) leadership has a positive and significant effect on employee performance, (2) organizational culture has a positive and significant effect on employee performance, (3) digital skills have a positive and significant effect on employee performance, (4) leadership, organizational culture and digital capabilities simultaneously have a positive and significant effect on employee performance. Due to limitations in time, financial resources, and other factors, this research is not without its imperfections. Future studies can expand by incorporating additional variables, increasing the sample size, and covering a broader geographical area.